Peran Generasi Muda dalam Membangun Budaya Integritas dan Pemberantasan Korupsi - Iwan Armawan; Pamtoro, Dodi Hadi; Edi Saneka; M. Archico Narendra; Muammar Eka Putra (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Corruption is an extraordinary crime that has systemic impacts on national life and governance. It not only causes financial losses to the state but also undermines the rule of law, damages democratic processes, and reduces the quality of sustainable development. This article aims to analyze the role of young generations in building a culture of integrity as an early prevention strategy against corruption. This study employs a literature review method by examining laws and regulations related to corruption, official reports from the Corruption Eradication Commission (KPK), and relevant scientific publications. The results indicate that strengthening individual integrity through the internalization of anti-corruption values, supported by systemic improvements and active youth participation, is a key factor in fostering a sustainable anti-corruption culture. Young generations act as agents of change through education, role modeling, social monitoring, and involvement in anti-corruption movements. Therefore, anti-corruption education serves as a crucial foundation in creating a clean and integrity-based society.